RISK FACTORS ASSOCIATED WITH POSTPARTUM OBSTETRIC DANGER SIGNS - erik ekowati; Nina Herlina (Universitas Airlangga, 2023)
Backgrounds: The postpartum period is approximately 40-42 days after giving birth, during which time there is a risk of complications for the mother. However, this is not realized by the mother because the main focus is caring for the baby. Therefore, mothers and families need to know the causes of the risk of postpartum danger. The purpose of this study was to determine the factors that cause danger signs during the puerperium so that appropriate and fast treatment doing. Method: The research design is analytic with a cross sectional approach. The study involved 70 postpartum and total sampling was based on age, knowledge, and family support. The results of the chi-square statistical test showed that there was a relationship between postpartum danger signs and education (p value = 0.003 OR = 6.413), knowledge (p value = 0.020, OR = 4.773) and family support (p value = 0.040, OR = 3.838). The result of the age variable is that there is no relationship (p value = 0.967 OR = 1.202). Conclusion: Postpartum based on their level of education, good knowledge and husband's support are able to detect danger signs during the postpartum so that the mother and baby are healthy.   Keywords: Risk factors obstetric, postpartum